A football helmet prototype that reduces linear and rotational acceleration with the addition of an outer shell - Zuckerman, Scott L. (J Neurosurg, 2018)
OBJECTIVE: Amid the public health controversy surrounding American football, a helmet that can reduce linear and rotational acceleration has the potential to decrease forces transmitted to the brain. The authors hypothesized that a football helmet with an outer shell would reduce both linear and rotational acceleration. The authors’ objectives were to 1) determine an optimal material for a shock-absorbing outer shell and 2) examine the ability of an outer shell to reduce linear and/or rotational acceleration. METHODS: A laboratory-based investigation was undertaken using an extra-large Riddell Revolution football helmet. Two materials (Dow Corning Dilatant Compound and Sorbothane) were selected for their non-Newtonian properties (changes in viscosity with shear stress) to develop an outer shell. External pads were attached securely to the helmet at 3 locations: the front boss, the side, and the back. The helmet was impacted 5 times per location at 6 m/sec with pneumatic ram testing. Two-sample t-tests were used to evaluate linear/rotational acceleration differences between a helmet with and a helmet without the outer shell. RESULTS: Sorbothane was superior to the Dow Corning compound in force reduction and recovered from impact without permanent deformation. Of 5 different grades, 70-duro (a unit of hardness measured with a durometer) Sorbothane was found to have the greatest energy dissipation and stiffness, and it was chosen as the optimal outer-shell material. The helmet prototype with the outer shell reduced linear acceleration by 5.8% (from 75.4g to 71.1g; p < 0.001) and 10.8% (from 89.5g to 79.8g; p = 0.033) at the side and front boss locations, respectively, and reduced rotational acceleration by 49.8% (from 9312.8 rad/sec(2) to 4671.7 rad/sed(2); p < 0.001) at the front boss location. CONCLUSIONS: Sorbothane (70 duro) was chosen as the optimal outer-shell material. In the outer-shell prototype helmet, the results demonstrated a 5%–10% reduction in linear acceleration at the side and front boss locations, and a 50% reduction in rotational acceleration at the front boss location. Given the paucity of publicly reported helmet-design literature and the importance of rotational acceleration in head injuries, the substantial reduction seen in rotational acceleration with this outer-shell prototype holds the potential for future helmet-design improvements.